Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi Menganalisis Simpanan Dana Deposito Kelas X Perbankan Syariah SMKN 2 Mojokerto - Ika Miftahurrohmah; Eko Wahjudi (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
The purpose of this study is to improve the learning outcomes of students by analyzing whether the teacher has implemented the PBL learning model properly, analyzing the study results of students through the PBL learning model, and analyzing the students' responses after the application of the PBL learning model. This study was classified as a classroom action research (PTK) type. CAR is a type of research where the main cause of the problem was in the classroom and can be felt directly by the teacher. Classroom Action Research which focused on classroom conditions is a methoud used in ths study using a model design from Kemmis Mc Taggart. The subjects of this research consisted of 33 pupils from class X Islamic Banking 1 in the 2018/2019 academic year. The findings of this study on the application of the PBL learning model on deposit material obtained a score of 71% in cycle I and 90% in cycle II, the achievement of student learning outcomes has increased with classical completeness obtained by 72% in cycle I and 90% in cycle II, and student responses show results Very good response with a score of 76.75% in cycle I and 83.75% in cycle II.